Unusual nasopharyngeal foreign body in a four-year-old child - Afridi, Arshad Ullah; Gohar, Muhammad Saeed; Imtiaz, Iqra; Bhatti, Hassan Majid (Journal of the Pakistan Medical Association, 2023)
Foreign bodies are amongst the commonest emergencies presenting to the otorhinolaryngologists. They can be remarkably difficult to see and remove. However, nasopharyngeal foreign bodies are exceedingly rare. Foreign bodies can have disastrous complications, such as rhinolith formation, septal perforation, erosion into the surrounding structures, and infections including sinusitis, otitis media, periorbital cellulitis, diphtheria, meningitis, and tetanus. Imaging investigations, such as X-ray, CT scan and MRI, can be of great help in diagnosing and planning treatment in clinically equivocal cases, although they are rarely needed. Complete removal of the foreign body is of paramount importance in treating this entity. This unique case demonstrates the importance of a thorough clinical examination and history in patients presenting with vague complaints, especially in the paediatric population due to their usually non-specific symptoms and insufficient history. Keywords: Foreign body, emergency, impaction.